The Effect of Attitude and Acceptability of Robot Use in Restaurants on Behavioral Intention - Ahmet Erdem; Mahmut Barakazı; Ferhat Şeker (Journal of Tourismology)
In recent years, it has been seen that technology-based tools have started to take place frequently in our daily lives. This situation is more prominent in organizations such as food and beverage producing human-oriented services. With the increase in technological awareness, it is observed that the tendency of individuals who are curious about creativity and innovation towards businesses that provide smart robotic services is increasing. The aim of this research is to determine the effect of attitude and acceptability of the use of robots in restaurants on behavioral intention. In line with the purpose of the research, relationships were determined with the help of data obtained from the scales developed on the subject. Based on the literature review, five hypotheses were developed. Relationships were tested with the path analysis created within the scope of structural equation modelling. The acceptability of robot use in restaurants by customers has a significant positive effect on behavioral intention, and this variable has the greatest effect on behavioral intention. In addition, “experience” and “advantage” dimensions of attitude towards robot use have significant positive effects, “disadvantage” dimension has a negative effect on behavioral intention. Lastly, according to R-square, 82.6% of behavioural intention is explained by attitudes and acceptability towards the use of robots in restaurants.